An Analysis of Representative Speech Acts Used in Covid-19 Speech in Queen Elizabeth II - Arsani, Anggie; Juniartha, I Wayan; Ariyaningsih, Ni Nyoman Deni (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study aims i). to find out the representative speech acts used in Queen Elizabeth II’s speech entitled Queen Urges ‘Self-Discipline and Resolve’ In Corona Virus Speech, ii). to analyse the meaning behind the utterance of Queen Elizabeth II’s speech entitled Queen Urges ‘Self-Discipline and Resolve’ In Corona Virus Speech. The analysis of the data uses qualitative method as the study presented descriptively according to theory of speech acts proposed by Searle (1976) to classify the representative speech acts and theory of contextual meaning proposed by Yule (1996) to analyse the meaning behind the utterances. The informal method is applied in presenting the result of the analysis. The result of this study shows that there are 20 of 28 utterances that identified as representative speech acts used in Queen Elizabeth II’s speech which means the speaker used representative the most in her speech.